Analisis Spritualitas dan Stres Kerja terhadap Perilaku Menyimpang di Tempat Kerja dengan Ketaqwaan sebagai Pemediasi di Kalangan Karyawan Universitas Jember - Catur Indah Sulistiyorini; Dwi Cahyono; Abadi Sanosra (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine directly or indirectly the influence of spirituality and stress on deviant behavior through piety as a variable that intervenes in Jember University employees. The number of samples in this study was 129. The analytical technique used was the Structural Equation Model (SEM) using WarpPLS 7.0. The results of data analysis show that spiritual variables have a significant effect on piety, work stress has a significant effect on piety, piety has a significant effect on deviant behavior, spirituality has a significant effect on deviant behavior, work stress has a significant effect on deviant behavior. Indirectly, spirituality and work stress have a significant effect on deviant behavior through piety. The conclusions from this study prove that there is a significant influence on all the variables examined in this study. Keywords: Piety, Deviant Behavior, Spirituality, Job Stress